Tingkat Kesehatan Bank Syariah di Indonesia - Pramono, Nugroho Heri; Azmi, Fika (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2023)
This study aims to empirically prove the influence of the Sharia Supervisory Board (DPS), the decision to go public, and the level of corruption on the soundness level of Islamic banks in Indonesia. The research method used is a quantitative method using secondary data. The population in this study are Islamic Commercial Banks registered at the OJK for the 2018-2020 period, totaling 12 Islamic banks. The sampling technique used was purposive sampling, and 36 observations were obtained. The data analysis method used was multiple linear regression analysis which was processed using SPSS 25. Based on the results of the study, DPS proxied by DPS education had a negative effect on the soundness level of Islamic banks proxied by NPF. However, DPS also has a positive effect on the soundness level of Islamic banks which is proxied by CAR. The results of other studies indicate that the go public policy has no effect on the soundness level of Islamic banks proxied by NPF but has a positive effect on the soundness level of Islamic banks proxied by CAR. In addition, the level of corruption has no effect on the soundness of Islamic banks, either proxied by NPF or CAR.